PERSEPSI MASYARAKAT TERHADAP PENAMBANGAN BATUGAMPING DI PT. SDIC PAPUA CEMENT INDONESIA MANOKWARI DITINJAU DARI SEGI BUDAYA - Maria A. I. Awandoi (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2018)
People in Doput village and Misapmeysi villages, based on their local knowlegde and understandings, have different points of view in perceiving problems resulted from mining activities, particularly impacts that have been experienced. In order to find out the villagers’ perception, a questionnaire consisted of questions about language, local knowledge, technology, art, traditional livelihood, religion, and kinship were distributed to 50 respondents in the two villages. The results showed that 74%– 88% of the respondents have good perception in terms of local culture. This is because the respondents assumed that the local culture still existed, and even would be preserved both before and after the limestone mining activities of PT. SDIC Papua Cement Indonesia Manokwari. The average percentage of cultural variables were perceived from good to very good; language (74%), natural knowledge (88%), tecnology (83%), art (74,67%), living livelihood traditional (83,33%), religion (85%), and kinship (84%). In general, the results indicated that the limestone mining in Maruni has been positively perceived by the villagers, espeecially from the culture perspective